CONTEXTUAL TEACHING AND LEARNING UNTUK MENINGKATAN PRESTASI BELAJAR MATEMATIKA MATERI PENJUMLAHAN SD NEGERI BUMIJO - Saskia, Nina Ari Mega; Purnomo, Heru; Lukitoaji, Beny Dwi (WIDYA DIDAKTIKA - Jurnal Ilmiah Kependidikan, 2024)
Every year, mathematics continues to evolve in line with the demands of the times, encouraging individuals to develop their creative skills or utilize mathematics as a crucial discipline. However, the academic achievement of students in two-digit addition at Bumijo Public Elementary School has not yet reached its optimal point. Only 51.85% of students have achieved scores above the Minimum Mastery Criteria (KKM), while 48.15% are still below it. This study employs Classroom Action Research with cycles aimed at enhancing students' learning achievements in this subject. Data were collected through testing techniques, observations, and documentation. Results from Cycle II indicate an improvement in student performance to 88.89%, with a mastery rate reaching 85.19%, meeting the established success indicator of 80%. The adoption of the CTL learning model in mathematics education is expected to provide a solution for improving teaching and learning outcomes in elementary schools by linking academic content with students' daily lives